Given: a 1 = 2 2 + 3 2 + 6 2
a 2 = 3 2 + 4 2 + 1 2 2
a 3 = 4 2 + 5 2 + 2 0 2
then a 1 2 4 = r 2 what is the value or r = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Recall that I = A 2 + B 2 + C 2 = ( A + B + C ) 2 − 2 ( A B + B C + C A ) which follows as a X r 2 = f r . a b o v e ( X + 1 ) 2 + ( X + 2 ) 2 + ( X + 1 ) 2 ( X + 2 ) 2 = s i m p l i f y ( X 2 + 5 X + 5 ) 2 − 4 ( X + 1 ) ( X + 2 ) 2 = s i m p l i f y ( X + 2 ) 4 − 2 ( X + 1 ) ( X + 2 ) 2 + ( X + 1 ) 2 = ( ( X + 2 ) 2 − ( X + 1 ) ) 2 = ( X 2 + 3 X + 3 ) 2 Thus, a 1 2 4 ( r ) = X ( X + 3 ) + 3 = 1 2 4 × 1 2 7 + 3 = 1 5 7 5 1
a n = x 2 + y 2 + z 2
a 1 2 4 = 1 2 5 2 + 1 2 6 2 + 1 5 7 5 0 2 = 2 4 8 0 9 4 0 0 1
r 2 = 2 4 8 0 9 4 0 0 1
r = 2 4 8 0 9 4 0 0 1 = 1 5 7 5 1
hence the answer is 1 5 7 5 1
Note: we have expressed x , y , z in form of a n as below.
x = n + 1
y = n + 2
z = ( x × y )
In my honest opinion, there should be written one more example - to the a 4 . This is important because there is more than one rule of understanding the rule, which I had at the beginning. I tried to make it in the way of thinking that to make the last basis of exponentiation in a n I should multiply the basis of exponentiation in the middle by 2 , and then add it to the last basis of exponentiation in a n − 1 . I hope you will understand what I mean ;). Btw. the answer for my rule is r = √ 6 2 7 5 7 9 0 1 :P
a n = ( n + 1 ) 2 + ( n + 2 ) 2 + ( ( n + 1 ) ( n + 2 ) ) 2 ⟹ a 1 2 4 = ( 1 2 5 ) 2 + ( 1 2 6 ) 2 + ( 1 2 5 × 1 2 6 ) 2 = r 2
⟹ r = 2 1 8 0 9 4 0 0 1
⟹ r = 1 5 7 5 1
Problem Loading...
Note Loading...
Set Loading...
Notice that a n = ( n + 1 ) 2 + ( n + 2 ) 2 + ( ( n + 1 ) ( n + 2 ) ) 2
= ( ( n + 1 ) ( n + 2 ) ) 2 + 2 n 2 + 6 n + 5
= ( ( n + 1 ) ( n + 2 ) ) 2 + 2 ( n 2 + 3 n + 2 ) + 1
= ( ( n + 1 ) ( n + 2 ) + 1 ) 2
So a 1 2 4 = ( 1 2 5 × 1 2 6 + 1 ) 2 , r = 1 5 7 5 1